ANALISIS EFEK TAPAK LOKAL DARI GEOLOGI TANAH DI BADUNG SELATAN DAN KOTA DENPASAR DENGAN SURVEI MIKROTREMOR (STUDI KASUS GEMPABUMI NUSADUA 13 OKTOBER 2011) - Mursitantyo, Adityo; Suarbawa, Komang Ngurah; Septiadhi, Ardhianto (BULETIN FISIKA; Vol 16 No 2 (2015): BULETIN FISIKA, 2015)
Local site effect from geology on South Badung and Denpasar City by microtremor measurements has been investigated. Ground predominant period was indicated by microtremor measurements with HVSR (Horizontal to Vertical Spectral Ratio) method. Subsoil A type was obtained by ground predominant period on Peguyangan, Pemecutan Kaja, Jimbaran, Uluwatu, and Jimbaran with ground predominant period range between 0.02 – 0.20 second. Subsoil B type was obtained on Canggu, Kerobokan, Denpasar City, Kesiman, Sanur, Sesetan, Kuta, Nusadua and Benoa Peninsula with ground predominant period range between 0.26 – 0.38 second. Subsoil C type was obtained on Seminyak, northern Sesetan and Sanur coast with ground predominant period range between 0.46 – 0.61 second. The conclusion, based on predominant period, geology, and data of damage due to October 13th 2011 Nusadua earthquake, areas with subsoil B and C type more susceptible than areas with subsoil A type when earthquake occur. Keywords : local site effect, microtremor, predominant period, HVSR